Biocompatibility of 3D-printed vs. thermoformed and heat-cured intraoral appliances - Weżgowiec, Joanna; Małysa, Andrzej; Szlasa, Wojciech; Kulbacka, Julita; Chwiłkowska, Agnieszka; Ziętek, Marek; Więckiewicz, Mieszko (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives: The development of additive manufacturing has the potential to revolutionize the fabrication of medical devices. This technology, also known as 3D printing, offers precise, cost-effective, and personalized approaches, which could be particularly beneficial in the production of intraoral appliances. Despite its promise, research on the biocompatibility of 3D-printed intraoral devices is still limited. Our study aims to address this gap. Methods: We examined the cytotoxicity of materials processed via three techniques commonly used for the fabrication of different intraoral appliances: 3D printing (Dental LT Clear), thermoforming (Duran adjusted with Durasplint LC), and conventional heat-curing (Villacryl H Plus). We also investigated the impact of chemical or UVC disinfection on the biocompatibility of these materials. We assessed the biological effects induced in human gingival fibroblasts (HGFs) through both direct contact tests (MTT and LDH assays) and extract tests (PrestoBlue, DCF, and cell death type assays). Additionally, we observed changes in cellular morphology and migration rate under an inverted light microscope. The surface roughness of materials was evaluated using contact profilometry. Statistical analysis was conducted using two-way analysis of variance. Results: Our findings suggest that all three fabrication techniques induced a slight cytotoxic effect in HGFs, as evidenced by both direct contact and extract tests. However, these materials could be considered nontoxic according to the ISO 10993-5:2009 norm, as the decrease in metabolic activity observed was always less than 30% compared to the untreated control. Conclusions: This novel study confirms that 3D printing may be a safe alternative to conventional methods for fabricating intraoral appliances. However, further tests assessing the long-term intraoral usage are still needed.